Magnetic Paste

The magnetic paste with small particle size magnetic powder and thermosetting resin addresses the issue of viscosity change during joining, enhancing filling properties and magnetic performance, thereby improving the manufacturing efficiency and quality of inductor components.

JP7647614B2Active Publication Date: 2025-03-18AJINOMOTO CO INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022014316
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-02-01
Publication Date
2025-03-18
Estimated Expiration
2042-02-01

AI Technical Summary

Technical Problem

Existing magnetic pastes with small particle size magnetic powders experience significant viscosity changes during joining, leading to reduced filling properties and decreased yield and productivity in circuit board manufacturing.

Method used

A magnetic paste comprising a small particle size magnetic powder and a thermosetting resin, with a specific moisture content and a high volume percentage of magnetic powder, is developed to minimize viscosity changes during joining.

Benefits of technology

The magnetic paste achieves stable viscosity, improved filling properties, and enhanced magnetic properties such as specific permeability and reduced magnetic loss, resulting in increased productivity and quality of inductor components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647614000004
    Figure 0007647614000004
  • Figure 0007647614000005
    Figure 0007647614000005
  • Figure 0007647614000006
    Figure 0007647614000006
Patent Text Reader

Abstract

To provide a magnetic paste that comprises small-diameter magnetic powder but shows little change in viscosity over time.SOLUTION: This magnetic paste includes (A) a magnetic powder, and (B) a thermosetting resin, wherein the (A) magnetic powder has an average particle diameter of 10 μm or less, and the moisture content of the magnetic paste is 1000 ppm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a magnetic paste and a method for producing the same, a cured product using the magnetic paste, a circuit board and a method for producing the same, and an inductor component. [Background technology]

[0002] In recent years, with the demand for smaller and thinner electronic devices, there is a demand for smaller circuit boards used in electronic devices and higher wiring density. As such circuit boards, there is a known type that is formed by filling through holes with a paste material.

[0003] For example, Patent Document 1 describes filling through holes in a circuit board for an inductor component with a magnetic paste containing magnetic particles such as iron oxide (III) and cobalt iron oxide. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-197624 A Summary of the Invention [Problem to be solved by the invention]

[0005] By filling the through-holes with the magnetic paste and hardening it, a magnetic layer can be formed in the through-holes. To improve the performance of inductor components, it is desirable for the magnetic layer to have high relative permeability and low magnetic loss. In general, a large particle size of magnetic powder is advantageous for achieving high permeability, but it tends to increase magnetic loss. Therefore, in order to simultaneously achieve high relative permeability and low magnetic loss, it is desirable for the magnetic paste to contain a high content of magnetic powder with a small particle size.

[0006] On the other hand, when filling holes with magnetic paste by a filling method such as printing, it is required to adjust the filling conditions according to the viscosity of the magnetic paste. However, the viscosity of the magnetic paste may change over time. When the viscosity of the magnetic paste changes over time, it is required to change the filling conditions each time the viscosity changes. The inventors have found that when using magnetic powder with a small particle size, the viscosity of the magnetic paste tends to increase significantly over time, and the problem of viscosity change over time becomes apparent. If the viscosity increase increases, the filling property decreases, which may result in a decrease in yield and productivity.

[0007] The present invention has been devised in view of the above-mentioned problems, and aims to provide a magnetic paste and a manufacturing method thereof that contains small particle size magnetic powder but has little change in viscosity over time; a hardened product of the magnetic paste; a circuit board including the hardened product of the magnetic paste and a manufacturing method thereof; and an inductor component including the circuit board. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above problems. As a result, the present inventors have found that a magnetic paste containing (A) small particle size magnetic powder and (B) thermosetting resin, and having a moisture content within a specific range, can solve the above problems, and have completed the present invention. That is, the present invention includes the following.

[0009] [1] A magnetic paste comprising (A) a magnetic powder and (B) a thermosetting resin, (A) the magnetic powder has an average particle size of 10 μm or less, A magnetic paste having a moisture content of 1000 ppm or less. [2] The magnetic paste according to [1], wherein the amount of the magnetic powder (A) relative to 100% by volume of the non-volatile components of the magnetic paste is 30% by volume or more. [3] The magnetic paste according to [1] or [2], wherein the thermosetting resin (B) includes an epoxy resin (B-1). [4] The magnetic paste according to [3], wherein the amount of the epoxy resin (B-1) relative to 100% by mass of the resin component of the magnetic paste is 30% by mass or more. [5] The magnetic paste according to any one of [1] to [4], further comprising (C) a hardening accelerator. [6] The magnetic paste according to any one of [1] to [5], which is for filling through-holes. [7] A hardened product of the magnetic paste according to any one of [1] to [6]. [8] A circuit board comprising a cured product of the magnetic paste according to any one of [1] to [6]. [9] A magnetic recording medium comprising: a substrate having a through hole formed therein; and a magnetic layer filled in the through hole; A circuit board, wherein the magnetic layer comprises a cured product of the magnetic paste according to any one of [1] to [6].

[10] An inductor component comprising the circuit board according to [8] or [9].

[11] A step of filling the holes of a substrate having holes formed therein with the magnetic paste according to any one of [1] to [6]; and hardening the magnetic paste filled in the holes.

[12] A method for producing a magnetic paste according to any one of [1] to [6], A step of mixing (A) a magnetic powder and (B) a thermosetting resin to obtain a paste-like composition; and drying the paste-like composition in a vacuum at an absolute pressure of 800 Pa or less. Effect of the Invention

[0010] According to the present invention, it is possible to provide a magnetic paste containing small particle size magnetic powder and having little change in viscosity over time, and a method for manufacturing the same; a hardened product of the magnetic paste; a circuit board including the hardened product of the magnetic paste and a method for manufacturing the same; and an inductor component including the circuit board. [Brief description of the drawings]

[0011] [Figure 1]FIG. 1 is a cross-sectional view that typically shows a core substrate before through-holes are formed in a method for manufacturing a circuit board according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view that typically shows a core base material in which a through hole is formed, in a method for producing a circuit board according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view that typically shows a core base material having a plating layer formed in a through-hole in a method for producing a circuit board according to one embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional view that typically shows a state in which a through-hole in a core substrate is filled with magnetic paste in a manufacturing method for a circuit board according to one embodiment of the present invention. [Diagram 5] FIG. 5 is a schematic cross-sectional view for explaining step (2) of the method for producing a circuit board according to one embodiment of the present invention. [Figure 6] FIG. 6 is a schematic cross-sectional view for explaining step (3) of the method for producing a circuit board according to one embodiment of the present invention. [Figure 7] FIG. 7 is a schematic cross-sectional view for explaining step (5) of the method for producing a circuit board according to one embodiment of the present invention. [Figure 8] FIG. 8 is a schematic cross-sectional view for explaining step (5) of the method for producing a circuit board according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the present invention will be described in detail with reference to the embodiments and examples. However, the present invention is not limited to the following embodiments and examples, and may be modified and implemented as desired without departing from the scope of the claims and their equivalents. In the following description, unless otherwise specified, the resin component of the magnetic paste refers to the non-volatile components of the magnetic paste excluding inorganic particles such as magnetic powder.

[0013] <Magnetic paste overview> The resin paste according to one embodiment of the present invention includes (A) a magnetic powder and (B) a thermosetting resin. The magnetic powder (A) has a small average particle size equal to or less than a specific value. The moisture content of the magnetic paste is in a small specific range.

[0014] The magnetic paste according to the present embodiment can reduce the change in viscosity during use while containing small (B) magnetic powder having an average particle size of a specific value or less. Therefore, when filling holes with the magnetic paste, the frequency of adjusting the filling conditions can be reduced. Therefore, a magnetic paste can be obtained that can easily be filled into holes while using small (B) magnetic powder. In addition, this magnetic paste can usually use small (B) magnetic powder and can contain a large amount of the (B) magnetic powder, so that it is possible to improve magnetic properties such as relative permeability and magnetic loss.

[0015] In the past, magnetic pastes containing small particle size magnetic powders have been considered. However, the conventional magnetic pastes were generally formed in layers on the surface of a substrate, and the magnetic layer was formed by hardening the magnetic paste layer. Such conventional magnetic layers did not require precise adjustment of viscosity.

[0016] In response to this, the present inventor prepared a substrate (hereinafter sometimes referred to as a "core substrate") with holes formed therein, filled the holes in the core substrate with a magnetic paste, and then cured the paste to form a magnetic layer. In order to fill the holes, precise adjustment of the viscosity is required. For example, in order to smoothly infiltrate the magnetic paste into the holes, it is required to lower the viscosity of the magnetic paste. On the other hand, when the holes are through holes that penetrate the core substrate, it is required to increase the viscosity of the magnetic paste so that the magnetic paste does not pass through the through holes and is not discharged. Therefore, in order to achieve both promotion of intrusion and suppression of discharge, precise control of the viscosity of the magnetic paste is required. However, the viscosity of the conventional magnetic paste changes over time, making it difficult to smoothly fill the holes. Thus, by examining the implementation method of a new technology of filling the holes formed in the core substrate with the magnetic paste, the problem of viscosity change over time became apparent for the first time.

[0017] The inventors of the present invention have conducted further research and found that the moisture content of a magnetic paste containing small particle size magnetic powder increases over time, and that the moisture content has a large effect on the viscosity change of the magnetic paste. In the magnetic paste according to the present embodiment, the moisture content in the magnetic paste is reduced to a specific value or less, thereby suppressing the viscosity change of the magnetic paste during the process.

[0018] <(A) Magnetic powder> The magnetic paste according to one embodiment of the present invention includes (A) magnetic powder as component (A). As the (A) magnetic powder, particles of a material having a relative magnetic permeability greater than 1 can be used. The material of the (A) magnetic powder is usually an inorganic material, and may be a soft magnetic material or a hard magnetic material. The material of the (A) magnetic powder may be used alone or in combination of two or more types. Thus, the (A) magnetic powder may be a soft magnetic powder, a hard magnetic powder, or a combination of a soft magnetic powder and a hard magnetic powder. The (A) magnetic powder may be used alone or in combination of two or more types. Among them, from the viewpoint of obtaining the effect of the present invention remarkably, it is preferable that the (A) magnetic powder includes a soft magnetic powder, and it is more preferable that the (A) magnetic powder includes only a soft magnetic powder.

[0019] (A) Examples of the magnetic powder include magnetic metal oxide powder and magnetic metal powder.

[0020] Examples of magnetic metal oxide powders include ferrite powders such as Fe-Mn ferrite powder, Fe-Mn-Mg ferrite powder, Fe-Mn-Mg-Sr ferrite powder, Fe-Mg-Zn ferrite powder, Fe-Mg-Sr ferrite powder, Fe-Zn-Mn ferrite powder, Fe-Cu-Zn ferrite powder, Fe-Ni-Zn ferrite powder, Fe-Ni-Zn-Cu ferrite powder, Fe-Ba-Zn ferrite powder, Fe-Ba-Mg ferrite powder, Fe-Ba-Ni ferrite powder, Fe-Ba-Co ferrite powder, Fe-Ba-Ni-Co ferrite powder, and Fe-Y ferrite powder; iron oxide powders such as iron oxide powder (III) and triiron tetroxide powder; and the like. Among these, ferrite powders are preferred. Ferrite powder is usually made of a composite oxide mainly composed of iron oxide, and is chemically stable. Therefore, ferrite powder has advantages such as high corrosion resistance, low risk of fire, and resistance to demagnetization. Among them, ferrite powder containing at least one element selected from the group consisting of Mn and Zn is preferred, ferrite powder containing Mn is more preferred, and Fe-Mn ferrite powder and Fe-Mn-Zn ferrite powder are particularly preferred. Fe-Mn ferrite powder refers to ferrite powder containing Fe and Mn, and Fe-Mn-Zn ferrite powder refers to ferrite powder containing Fe, Mn, and Zn.

[0021] Examples of magnetic metal powders include pure iron powder; crystalline or amorphous alloy powders such as Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Cr alloy powder, Fe-Cr-Si alloy powder, Fe-Ni-Cr alloy powder, Fe-Cr-Al alloy powder, Fe-Ni alloy powder, Fe-Ni-Si alloy powder, Fe-Ni-B alloy powder, Fe-Ni-Mo alloy powder, Fe-Ni-Mo-Cu alloy powder, Fe-Co alloy powder, Fe-Ni-Co alloy powder, and Co-based amorphous alloy powder; and the like. Among them, alloy powders are preferred, and iron alloy powders are more preferred. As the iron alloy powder, iron alloy powders containing Fe and at least one element selected from the group consisting of Si, Cr, and Ni are preferred, and Fe-Cr-Si alloy powder and Fe-Ni alloy powder are particularly preferred. The Fe-Cr-Si alloy powder refers to an alloy powder containing Fe, Cr and Si, and the Fe-Ni alloy powder refers to an alloy powder containing Fe and Ni.

[0022] (A) As the magnetic powder, commercially available magnetic powders may be used. Some commercially available magnetic powders may not have an average particle size smaller than a specific value, but such magnetic powders may be used after being classified, pulverized, or otherwise processed to reduce the average particle size. Specific examples of commercially available magnetic powders include "M05S", "M001", and "MZ05S" manufactured by Powdertech Co., Ltd.; "PST-S" manufactured by Sanyo Special Steel Co., Ltd.; "AW2-08", "AW2-08PF20F", "AW2-08PF10F", "AW2-08PF3F", "Fe-3.5Si-4.5CrPF20F", "Fe-50NiPF20F", and "Fe-80Ni-4MoPF20F" manufactured by Epson Atmix; and "LD-M", "LD-MH", "KNI-106", "KNI-106GSM", "KNI-106GS", and "KNI -109", "KNI-109GSM", "KNI-109GS"; "KNS-415", "BSF-547", "BSF-029", "BSN-125", "BSN-125", "BSN-714", "BSN-828", "S-1281", "S-1641", "S-1651", "S-1470", "S-1511", "S-2430" manufactured by Toda Kogyo Co., Ltd.; "JR09P2" manufactured by Japan Metals and Chemical Industries Co., Ltd.; "Nanotek" manufactured by CIK Nanotech Co., Ltd.; "JEMK-S" and "JEMK-H" manufactured by Kinsei Matec Co., Ltd.; "Yttrium iron oxide" manufactured by ALDRICH Co., Ltd.; "MA-RCO-5" manufactured by DOWA Electronics Co., Ltd.; and the like. (A) Magnetic powder may be used alone or in combination of two or more types.

[0023] The (A) magnetic powder usually has an average particle size of 10 μm or less. In detail, the range of the average particle size of the (A) magnetic powder is usually 10 μm or less, preferably 9 μm or less, more preferably 8 μm or less, even more preferably 7 μm or less, even more preferably 6 μm or less, and particularly preferably 5 μm or less. The magnetic paste according to this embodiment can suppress the problem of the viscosity change over time that is manifested in the magnetic paste containing the (A) magnetic powder having a small particle size. In addition, when the (A) magnetic paste having a small particle size is used, the magnetic loss of the hardened material of the magnetic paste can usually be suppressed. The lower limit of the average particle size of the (A) magnetic powder is not particularly limited, but may be, for example, 0.05 μm or more, 0.5 μm or more, 1 μm or more, etc.

[0024] Unless otherwise specified, the average particle size refers to the median diameter based on volume. This average particle size can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, a particle size distribution based on volume can be created using a laser diffraction / scattering particle size distribution measuring device, and the median diameter can be measured as the average particle size. The measurement sample is preferably a powder dispersed in water using ultrasonic waves. Examples of laser diffraction / scattering particle size distribution measuring devices that can be used include the LA-500 manufactured by Horiba, Ltd. and the SALD-2200 manufactured by Shimadzu Corporation.

[0025] (A) The specific surface area of ​​the magnetic powder is preferably 0.05 m from the viewpoint of improving the relative magnetic permeability. 2 / g or more, more preferably 0.1m 2 / g or more, more preferably 0.3m 2 / g or more, preferably 10m 2 / g or less, more preferably 8m 2 / g or less, more preferably 5m 2 / g or less. (A) The specific surface area of ​​the magnetic powder can be measured by the BET method. Specifically, the specific surface area can be measured by the BET method using a specific surface area measuring device ("Macsorb HM Model 1210" manufactured by Mountech Co., Ltd.) to adsorb nitrogen gas onto the surface of the sample and using the BET multipoint method.

[0026] The particles of the magnetic powder (A) are preferably spherical or ellipsoidal. The aspect ratio of the length of the major axis of the particles of the magnetic powder (A) divided by the length of the minor axis is preferably 2 or less, more preferably 1.5 or less, and even more preferably 1.2 or less, and is usually 1.0 or more. In general, when the shape of the particles of the magnetic powder is flat and not spherical, it is easy to improve the relative magnetic permeability. On the other hand, when the shape of the particles of the magnetic powder is close to spherical, it is easy to reduce the magnetic loss.

[0027] (A) The true specific gravity of the magnetic powder is, for example, 4 g / cm 3 ~10g / cm 3 It is possible.

[0028] The amount (volume %) of the (A) magnetic powder contained in the magnetic paste is preferably 30% by volume or more, more preferably 40% by volume or more, particularly preferably 50% by volume or more, and preferably 95% by volume or less, more preferably 85% by volume or less, particularly preferably 75% by volume or less, based on 100% by volume of the non-volatile components of the magnetic paste. When the amount (volume %) of the (A) magnetic powder is in the above range, the viscosity change during joining has tended to be particularly large in the past, but the magnetic paste according to this embodiment can suppress the viscosity change during joining. Also, when the amount (volume %) of the (A) magnetic powder is in the above range, the viscosity of the magnetic paste can usually be appropriately adjusted to increase the filling property, or effectively improve the magnetic properties such as the relative magnetic permeability and magnetic loss.

[0029] The volumetric amount (volume %) of each component contained in the magnetic paste is calculated from the mass of the component contained in the magnetic paste. Specifically, the mass is divided by the specific gravity to obtain the volume of each component, and the volumetric amount (volume %) can be calculated from the volume of each component thus obtained.

[0030] The amount (mass%) of the (A) magnetic powder contained in the magnetic paste is preferably 60% by mass or more, more preferably 70% by mass or more, particularly preferably 80% by mass or more, and preferably 99% by mass or less, more preferably 95% by mass or less, particularly preferably 92% by mass or less, based on 100% by mass of the non-volatile components of the magnetic paste. When the amount (mass%) of the (A) magnetic powder is in the above range, the viscosity change during joining has been particularly large in the past, but the magnetic paste according to this embodiment can suppress the viscosity change during joining. Also, when the amount (mass%) of the (A) magnetic powder is in the above range, the viscosity of the magnetic paste can usually be appropriately adjusted to increase the filling property, or effectively improve the magnetic properties such as the relative magnetic permeability and magnetic loss.

[0031] <(B) Thermosetting resin> The magnetic paste according to one embodiment of the present invention contains a thermosetting resin (B) as component (B). The thermosetting resin (B) can usually bind the magnetic powder (A). The thermosetting resin (B) usually reacts with heat to form bonds, and can harden the magnetic paste. Thus, the magnetic paste containing the magnetic powder (A) and the thermosetting resin (B) in combination can harden to form a magnetic layer.

[0032] Examples of the (B) thermosetting resin include epoxy resins, phenolic resins, active ester resins, amine resins, acid anhydride resins, benzoxazine resins, cyanate ester resins, carbodiimide resins, etc. The (B) thermosetting resins may be used alone or in combination of two or more.

[0033] The (B) thermosetting resin preferably contains (B-1) epoxy resin. (B-1) epoxy resin refers to a resin having one or more epoxy groups in the molecule. When the (B) thermosetting resin contains (B-1) epoxy resin, the viscosity change of the magnetic paste during the process can be effectively suppressed, and usually the magnetic properties of the cured product can be effectively improved.

[0034] Examples of the (B-1) epoxy resin include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, phenol novolac type epoxy resins, glycidyl amine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, alicyclic epoxy resins having an ester skeleton, Examples of the epoxy resin include heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, naphthylene ether type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, naphthol novolac type epoxy resins, and other epoxy resins containing a condensed ring skeleton, isocyanurate type epoxy resins, alkyleneoxy skeleton and butadiene skeleton-containing epoxy resins, and fluorene structure-containing epoxy resins. The epoxy resin (B-1) may be used alone or in combination of two or more.

[0035] The epoxy resin (B-1) preferably contains an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule relative to the total amount of the epoxy resin (B-1) (100% by mass) is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.

[0036] (B-1) Epoxy resin preferably has an aromatic structure. When two or more kinds of epoxy resins are used, it is preferable that one or more kinds of epoxy resins have an aromatic structure. The aromatic structure is a chemical structure generally defined as aromatic, and includes polycyclic aromatic rings and aromatic heterocycles.

[0037] (B-1) epoxy resins include epoxy resins that are liquid at a temperature of 20°C (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20°C (hereinafter sometimes referred to as "solid epoxy resins"). (B-1) epoxy resin may be only a liquid epoxy resin, may be only a solid epoxy resin, or may be a combination of a liquid epoxy resin and a solid epoxy resin. In particular, (B-1) epoxy resin preferably contains a liquid epoxy resin, and particularly preferably contains only a liquid epoxy resin.

[0038] As the liquid epoxy resin, liquid epoxy resin having two or more epoxy groups in one molecule is preferred.As the liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having ester skeleton, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, epoxy resin having butadiene structure, epoxy resin containing alkyleneoxy skeleton and butadiene skeleton, epoxy resin containing fluorene structure, dicyclopentadiene type epoxy resin is preferred.Among them, bisphenol A type epoxy resin, bisphenol F type epoxy resin, and cyclohexane type epoxy resin are particularly preferred.

[0039] Specific examples of liquid epoxy resins include "YX7400" manufactured by Mitsubishi Chemical Corporation; "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "jER828EL", "825", and "Epicoat 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", and "604" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA Corporation; "EP-3950L" and "EP-3980S" (glycidylamine type epoxy resins) manufactured by ADEKA Corporation; and "EP-4088S" (disilicide type epoxy resins) manufactured by ADEKA Corporation. bisphenol A type epoxy resin); "ZX-1059" manufactured by Nippon Steel Chemical & Material Co., Ltd. (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin); "EX-721" manufactured by Nagase ChemteX Corporation (glycidyl ester type epoxy resin); "EX-991L" manufactured by Nagase ChemteX Corporation (alkyleneoxy skeleton-containing epoxy resin); "Celloxide 2021P" and "Celloxide 2081" manufactured by Daicel Corporation (alicyclic epoxy resin with ester skeleton); "PB-3600" manufactured by Daicel Corporation, "JP-100" and "JP-200" manufactured by Nippon Soda Co., Ltd. (epoxy resin with butadiene structure); "ZX-1658" and "ZX-1658GS" manufactured by Nippon Steel Chemical & Material Co., Ltd. (liquid 1,4-glycidylcyclohexane type epoxy resin); "EG-280" manufactured by Osaka Gas Chemical Co., Ltd. (fluorene structure-containing epoxy resin); and the like. The liquid epoxy resin may be used alone or in combination of two or more kinds.

[0040] As the solid epoxy resin, the solid epoxy resin having three or more epoxy groups in one molecule is preferable, and the aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.As the solid epoxy resin, the bixylenol type epoxy resin, the naphthalene type epoxy resin, the naphthalene type 4-functional epoxy resin, the cresol novolac type epoxy resin, the dicyclopentadiene type epoxy resin, the trisphenol type epoxy resin, the naphthol type epoxy resin, the biphenyl type epoxy resin, the naphthylene ether type epoxy resin, the anthracene type epoxy resin, the bisphenol A type epoxy resin, the bisphenol AF type epoxy resin, the tetraphenylethane type epoxy resin is preferable, and the dicyclopentadiene type epoxy resin is particularly preferable.

[0041] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; and "HP-7200", "HP-7200HH", and "HP-7200H" (dicyclopentadiene type epoxy resins) manufactured by DIC Corporation. DIC's "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", and "HP6000" (naphthylene ether type epoxy resins); Nippon Kayaku's "EPPN-502H" (trisphenol type epoxy resin); Nippon Kayaku's "NC7000L" (naphthol novolac type epoxy resin); Nippon Kayaku's "NC3000H", "NC3000", "NC3000L", and "NC3100" (biphenyl type epoxy resins) resin); "ESN475V" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX4000HK" (bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; Examples of the epoxy resins include "YX7700" (xylene structure-containing novolac type epoxy resin) manufactured by Osaka Gas Chemicals Co., Ltd.; "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1010" (solid bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation. The solid epoxy resins may be used alone or in combination of two or more kinds.

[0042] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin, the mass ratio of the liquid epoxy resin to the solid epoxy resin (liquid epoxy resin / solid epoxy resin) is preferably 0.5 or more, more preferably 1 or more, even more preferably 5 or more, and particularly preferably 10 or more.

[0043] The epoxy equivalent of the (B-1) epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 110 g / eq. to 1000 g / eq. The epoxy equivalent is the mass of a resin containing one equivalent of an epoxy group. This epoxy equivalent can be measured according to JIS K7236.

[0044] The weight average molecular weight (Mw) of the epoxy resin (B-1) is preferably from 100 to 5000, more preferably from 250 to 3000, and further preferably from 400 to 1500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.

[0045] The amount (mass%) of the (B-1) epoxy resin contained in the magnetic paste is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, particularly preferably 1 mass% or more, and preferably 30 mass% or less, more preferably 20 mass% or less, particularly preferably 15 mass% or less, based on 100 mass% of the non-volatile components of the magnetic paste. When the amount of the (B-1) epoxy resin is within the above range, the viscosity change during the joining of the magnetic paste can be effectively suppressed, and usually the magnetic properties of the cured product can be effectively improved.

[0046] The amount (mass%) of the (B-1) epoxy resin contained in the magnetic paste is preferably 10 mass% or more, more preferably 20 mass% or more, particularly preferably 30 mass% or more, and is preferably 99 mass% or less, more preferably 98 mass% or less, particularly preferably 97 mass% or less, based on 100 mass% of the resin component of the magnetic paste. When the amount of the (B-1) epoxy resin is within the above range, the viscosity change during the joining of the magnetic paste can be effectively suppressed, and usually the magnetic properties of the cured product can be effectively improved.

[0047] When the (B) thermosetting resin contains the (B-1) epoxy resin, the (B) thermosetting resin may contain a resin capable of reacting with the (B-1) epoxy resin to bond. The resin capable of reacting with the (B-1) epoxy resin to bond may be hereinafter referred to as "(B-2) curing agent". Examples of the (B-2) curing agent include phenol-based resins, active ester-based resins, amine-based resins, carbodiimide-based resins, acid anhydride-based resins, benzoxazine-based resins, cyanate ester-based resins, and thiol-based resins. The (B-2) curing agent may be used alone or in combination of two or more types.

[0048] As the phenolic resin, a resin having one or more, preferably two or more, hydroxyl groups bonded to an aromatic ring such as a benzene ring or a naphthalene ring in one molecule can be used. From the viewpoint of heat resistance and water resistance, a phenolic resin having a novolac structure is preferred. From the viewpoint of adhesion, a nitrogen-containing phenolic resin is preferred, and a triazine skeleton-containing phenolic resin is more preferred. Among them, from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion, a triazine skeleton-containing phenolic novolac resin is preferred.

[0049] Specific examples of phenolic resins include "MEH-7700", "MEH-7810", "MEH-7851", and "MEH-8000H" manufactured by Meiwa Chemical Industry Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; and "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-495V", "SN-375", and "SN" manufactured by Nippon Steel Chemical & Material Co., Ltd. -395"; "TD-2090", "TD-2090-60M", "LA-7052", "LA-7054", "LA-1356", "LA-3018", "LA-3018-50P", "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", and "KA-1165" manufactured by DIC Corporation; "GDP-6115L", "GDP-6115H", and "ELPC75" manufactured by Gun-ei Chemical Co., Ltd.

[0050] As the active ester resin, a compound having one or more, preferably two or more active ester groups in one molecule can be used. Among them, as the active ester resin, a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferred. The active ester resin is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester resin obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester resin obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.

[0051] Preferred specific examples of the active ester resin include active ester resins containing a dicyclopentadiene-type diphenol structure, active ester resins containing a naphthalene structure, active ester resins containing an acetylated product of phenol novolac, and active ester resins containing a benzoylated product of phenol novolac. Among them, active ester resins containing a naphthalene structure and active ester resins containing a dicyclopentadiene-type diphenol structure are more preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.

[0052] Commercially available active ester resins include active ester resins containing a dicyclopentadiene-type diphenol structure, such as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "EXB-8000L-65TM" (manufactured by DIC Corporation); active ester resins containing a naphthalene structure, such as "EXB-9416-70BK", "EXB-8150-65T", "EXB-8100L-65T", and "EXB-8150L-65T" (manufactured by DIC Corporation); and phenol novolac Examples of active ester resins containing acetylated compounds include "DC808" (manufactured by Mitsubishi Chemical Corporation); examples of active ester resins containing benzoylated phenol novolac include "YLH1026" (manufactured by Mitsubishi Chemical Corporation); examples of active ester resins which are acetylated phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Corporation); and examples of active ester resins which are benzoylated phenol novolac include "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), and "YLH1048" (manufactured by Mitsubishi Chemical Corporation).

[0053] As the amine resin, a resin having one or more, preferably two or more, amino groups in one molecule can be used. Examples of the amine resin include aliphatic amines, polyether amines, alicyclic amines, and aromatic amines. Among them, aromatic amines are preferred. The amine resin is preferably a primary amine or a secondary amine, and more preferably a primary amine. Specific examples of the amine resin include 4,4'-methylenebis(2,6-dimethylaniline), diphenyldiaminosulfone, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxyphenyl)-2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, and 2,2-bis(3-amino-4-hydroxyphenyl)-2,2'-dimethyl-4,4'-diaminobiphenyl. phenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. As the amine-based resin, commercially available products may be used, for example, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.

[0054] As the carbodiimide resin, a resin having one or more, preferably two or more, carbodiimide structures in one molecule can be used. Specific examples of the carbodiimide resin include aliphatic biscarbodiimides such as tetramethylene-bis(t-butylcarbodiimide) and cyclohexane bis(methylene-t-butylcarbodiimide); aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide); poly(phenylenecarbodiimide), poly(naphthalenecarbodiimide), and the like. Examples of polycarbodiimides include aromatic polycarbodiimides such as poly(methylenediphenylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and poly[methylenebis(methylphenylene)carbodiimide]. Commercially available carbodiimide resins include, for example, "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07" and "Carbodilite V-09" manufactured by Nisshinbo Chemical Inc.; and "Stavaxol P", "Stavaxol P400" and "Hi-Kasil 510" manufactured by Rhein Chemie.

[0055] As the acid anhydride resin, a resin having one or more acid anhydride groups in one molecule can be used, and a resin having two or more acid anhydride groups in one molecule is preferable. Specific examples of the acid anhydride resin include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, and benzophenonetetracarboxylic dianhydride. Examples of acid anhydrides include anhydrides, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid. Commercially available acid anhydride resins include, for example, "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by New Japan Chemical Co., Ltd.; "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation; "HN-2200" and "HN-5500" manufactured by Hitachi Chemical Co., Ltd.; and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Clay Valley Corporation.

[0056] Specific examples of benzoxazine resins include "JBZ-OD100", "JBZ-OP100D", and "ODA-BOZ" manufactured by JFE Chemical Corporation; "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.; and "HFB2006M" manufactured by Showa Polymer Co., Ltd.

[0057] Examples of cyanate ester resins include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester resins include "PT30" and "PT60" (phenol novolac type multifunctional cyanate ester resins), "ULL-950S" (multifunctional cyanate ester resin), "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.

[0058] Examples of thiol-based resins include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.

[0059] The active group equivalent of the (B-2) curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The active group equivalent represents the mass of the (B-2) curing agent per equivalent of the active group.

[0060] When the number of epoxy groups in the (B-1) epoxy resin is 1, the number of active groups in the (B-2) curing agent is preferably 0.01 or more, more preferably 0.1 or more, particularly preferably 0.5 or more, and preferably 10 or less, more preferably 5 or less, particularly preferably 3 or less. The active groups in the (B-2) curing agent are active hydroxyl groups and the like, and vary depending on the type of curing agent. The number of epoxy groups in the (B-1) epoxy resin is the total value of the solid content mass of each epoxy resin divided by the epoxy equivalent for all epoxy resins. The number of active groups in the (B-2) curing agent is the total value of the solid content mass of each curing agent divided by the active group equivalent for all curing agents.

[0061] The amount (mass%) of the (B-2) hardener contained in the magnetic paste is preferably 0.1 mass% or more, more preferably 0.25 mass% or more, particularly preferably 0.5 mass% or more, and preferably 20 mass% or less, more preferably 10 mass% or less, particularly preferably 5 mass% or less, based on 100 mass% of the non-volatile components of the magnetic paste. When the amount of the (B-2) hardener is within the above range, the viscosity change during the continuation of the magnetic paste can be effectively suppressed, and usually the magnetic properties of the cured product can be effectively improved.

[0062] The amount (mass%) of the (B-2) hardener contained in the magnetic paste is preferably 1 mass% or more, more preferably 2.5 mass% or more, particularly preferably 5 mass% or more, and preferably 50 mass% or less, more preferably 30 mass% or less, particularly preferably 20 mass% or less, relative to 100 mass% of the resin component of the magnetic paste. When the amount of the (B-2) hardener is within the above range, the viscosity change during the joining of the magnetic paste can be effectively suppressed, and usually the magnetic properties of the cured product can be effectively improved.

[0063] When (B) thermosetting resins are classified by viscosity, it is preferable that (B) thermosetting resin contains a reactive diluent. The reactive diluent refers to a component of (B) thermosetting resin that has a low viscosity. The specific viscosity of the reactive diluent is usually less than 0.5 Pa·s. There is no particular limit to the lower limit of the viscosity of the reactive diluent, and it can be, for example, 0.001 Pa·s or more, 0.005 Pa·s or more, 0.01 Pa·s or more, etc. The viscosity of the reactive diluent can be measured using an E-type viscometer at 25±2°C. When (B) thermosetting resin contains a reactive diluent, the viscosity of the magnetic paste can be reduced.

[0064] The reactive diluent may contain reactive groups such as the above-mentioned epoxy group and active group.Preferable examples of the reactive group contained in the reactive diluent include epoxy group, acrylic group, methacryl group, oxetane group, etc., among which epoxy group is preferred.Therefore, it is preferred to use the epoxy resin (B-1) having low viscosity as the reactive diluent.

[0065] Examples of commercially available reactive diluents include "EX-201" (alicyclic glycidyl ether), EX-830, EX-821 (ethylene glycol type epoxy resin), and EX-212 (hexanediol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane); "EP-3980S" (glycidylamine type epoxy resin), "EP-4088S", "EP-4088L" (dicyclopentadiene type epoxy resin), and ED-509S (tert-butylphenyl glycidyl ether) manufactured by ADEKA Corporation; and X-22-163 (siloxane type epoxy resin) manufactured by Shin-Etsu Chemical Co., Ltd. The reactive diluent may be used alone or in combination of two or more types.

[0066] The amount (mass%) of the reactive diluent contained in the magnetic paste is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, particularly preferably 1 mass% or more, and preferably 20 mass% or less, more preferably 10 mass% or less, particularly preferably 7 mass% or less, based on 100 mass% of the non-volatile components of the magnetic paste. When the amount of the reactive diluent is within the above range, the viscosity change of the magnetic paste during the joining can be effectively suppressed, and usually the viscosity of the magnetic paste can be reduced and the magnetic properties of the cured product can be effectively improved.

[0067] The amount (mass %) of the reactive diluent contained in the magnetic paste is preferably 1 mass % or more, more preferably 5 mass % or more, particularly preferably 10 mass % or more, and preferably 90 mass % or less, more preferably 80 mass % or less, particularly preferably 50 mass % or less, relative to 100 mass % of the resin component of the magnetic paste. When the amount of the reactive diluent is within the above range, the viscosity change of the magnetic paste during the joining can be effectively suppressed, and usually the viscosity of the magnetic paste can be reduced and the magnetic properties of the cured product can be effectively improved.

[0068] The amount (mass %) of the reactive diluent contained in the magnetic paste is preferably 1 mass % or more, more preferably 5 mass % or more, particularly preferably 10 mass % or more, and preferably 100 mass % or less, more preferably 75 mass % or less, particularly preferably 50 mass % or less, based on 100 mass % of the (B) thermosetting resin. When the amount of the reactive diluent is within the above range, the viscosity change of the magnetic paste during joining can be effectively suppressed, and usually the viscosity of the magnetic paste can be reduced and the magnetic properties of the cured product can be effectively improved.

[0069] The weight average molecular weight (Mw) range of the (B) thermosetting resin can usually be the same as the range of the weight average molecular weight of the (B-1) epoxy resin described above.

[0070] The amount (mass%) of the (B) thermosetting resin contained in the magnetic paste is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, particularly preferably 1 mass% or more, and preferably 30 mass% or less, more preferably 20 mass% or less, particularly preferably 15 mass% or less, based on 100 mass% of the non-volatile components of the magnetic paste. When the amount of the (B) thermosetting resin is within the above range, the viscosity change during the joining of the magnetic paste can be effectively suppressed, and usually the magnetic properties of the cured product can be effectively improved.

[0071] The amount (mass%) of the (B) thermosetting resin contained in the magnetic paste is preferably 10 mass% or more, more preferably 20 mass% or more, particularly preferably 30 mass% or more, and is preferably 99 mass% or less, more preferably 98 mass% or less, particularly preferably 97 mass% or less, based on 100 mass% of the resin component of the magnetic paste. When the amount of the (B) thermosetting resin is within the above range, the viscosity change during the joining of the magnetic paste can be effectively suppressed, and usually the magnetic properties of the cured product can be effectively improved.

[0072] <(C) Curing accelerator> The magnetic paste according to one embodiment of the present invention may further contain (C) a hardening accelerator as an optional component in combination with the above-mentioned (A) to (B) components. The (C) hardening accelerator as this (C) component does not include those corresponding to the above-mentioned (A) to (B) components. The (C) hardening accelerator functions as a catalyst that accelerates the hardening of the (B-1) epoxy resin, and therefore can accelerate the hardening of the magnetic paste. In addition, in general, conventional magnetic pastes containing hardening accelerators tend to increase in viscosity as the reaction of the (B) thermosetting resin progresses over time, but the magnetic paste according to this embodiment is usually capable of suppressing viscosity changes over time even when it contains the (C) hardening accelerator.

[0073] Examples of the (C) curing accelerator include phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. Among these, imidazole-based curing accelerators are preferred. The (C) curing accelerators may be used alone or in combination of two or more.

[0074] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2, 4-Diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-furan Examples of the imidazole compounds include imidazole compounds such as 2-ethyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins. Of these, 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole are preferred. As the imidazole-based curing accelerator, commercially available products may be used, such as "P200-H50" manufactured by Mitsubishi Chemical Corporation; and "Curezol 2MZ", "2E4MZ", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", "Cl1Z-A", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2MZA-PW", "2PHZ", and "2PHZ-PW" manufactured by Shikoku Chemical Industry Co., Ltd.

[0075] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, 1,8-diazabicyclo[5,4,0]undecene-7,4-dimethylaminopyridine, and 2,4,6-tris(dimethylaminomethyl)phenol, with 4-dimethylaminopyridine being preferred.

[0076] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, and the like, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.

[0077] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene. Examples of such biguanide include o-[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Of these, dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.

[0078] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0079] The amount (mass %) of the (C) hardening accelerator contained in the magnetic paste may be 0 mass % or may be greater than 0 mass %, and is preferably 0.001 mass % or more, more preferably 0.01 mass % or more, and particularly preferably 0.1 mass % or more, and is preferably 5 mass % or less, more preferably 3 mass % or less, and particularly preferably 1 mass % or less, relative to 100 mass % of the non-volatile components of the magnetic paste.

[0080] The amount (mass %) of the (C) hardening accelerator contained in the magnetic paste may be 0 mass % or may be greater than 0 mass %, relative to 100 mass % of the resin component of the magnetic paste, and is preferably 0.01 mass % or more, more preferably 0.1 mass % or more, and particularly preferably 1 mass % or more, and is preferably 20 mass % or less, more preferably 15 mass % or less, and particularly preferably 10 mass % or less.

[0081] <(D) Dispersant> The magnetic paste according to one embodiment of the present invention may further contain a dispersant (D) as an optional component in combination with the above-mentioned components (A) to (C). The dispersant (D) as the component (D) does not include any of the above-mentioned components (A) to (C). The dispersant (D) can effectively increase the dispersibility of the magnetic powder (A), and therefore can effectively reduce the viscosity of the magnetic paste.

[0082] There is no limitation on the type of (D) dispersant. For example, the (D) dispersant may contain a functional group capable of adsorbing to the (A) magnetic powder, and disperse the (A) magnetic powder by repulsion between the (D) dispersants (e.g., electrostatic repulsion, steric repulsion, etc.) when adsorbed to the (A) magnetic powder. Examples of such (D) dispersants include acidic dispersants and basic dispersants.

[0083] The acidic dispersant usually contains an acidic functional group such as a carboxyl group, a sulfo group (-SO3H), a sulfate group (-OSOH), a phosphono group (-PO(OH)2), a phosphonooxy group (-OPO(OH)2), a hydroxyphosphoryl group (-PO(OH)-), or a sulfanyl group (-SH). The acidic functional group usually has a dissociable proton, and may be neutralized with a base such as an amine or a hydroxide ion. Preferred examples of the acidic dispersant include acidic polymer dispersants containing a polymer chain such as a polyoxyalkylene chain or a polyether chain. Preferred examples of acidic dispersants include "C-2093I" and "SC-1015F (a polyfunctional comb-type functional polymer having an ionic group in the main chain and a polyoxyalkylene chain in the graft chain)" manufactured by NOF Corporation; "DA-375 (a polyether phosphate ester compound-based dispersant)" manufactured by Kusumoto Chemical Industries Co., Ltd.; "RS-410", "RS-610", and "RS-710" (pH 1.9) (phosphate ester-based dispersant) from the "Phosphanol" series manufactured by Toho Chemical Industry Co., Ltd.; and "AKM-0531", "AFB-1521", "SC-0505K", and "SC-0708A" from the "Marialim" series manufactured by NOF Corporation.

[0084] The basic dispersant usually contains basic functional groups such as primary, secondary and tertiary amino groups; ammonium groups; imino groups; and nitrogen-containing heterocyclic groups such as pyridine, pyrimidine, pyrazine, imidazole and triazole. The basic functional groups may be neutralized with an acid such as an organic acid or an inorganic acid. A preferred basic dispersant is, for example, a basic polymer dispersant containing a polymer chain such as a polyester chain. A preferred example of the basic dispersant is "Ajisper PB881" (polyamine-based dispersant containing a polyester chain) manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0085] The dispersant (D) may be used alone or in combination of two or more kinds.

[0086] The amount (mass%) of the dispersant (D) contained in the magnetic paste may be 0 mass% or more, and is preferably 0.01 mass% or more, more preferably 0.1 mass% or more, particularly preferably 0.2 mass% or more, and is preferably 5 mass% or less, more preferably 3 mass% or less, and particularly preferably 2 mass% or less, based on 100 mass% of the non-volatile components of the magnetic paste. When the amount of the dispersant (D) is within the above range, the viscosity of the magnetic paste can be reduced. In addition, it is usually possible to effectively suppress the viscosity change during the continuation of the magnetic paste, and to effectively improve the magnetic properties of the cured product.

[0087] The amount (mass%) of the (D) dispersant contained in the magnetic paste may be 0 mass% or more, and is preferably 0.1 mass% or more, more preferably 1 mass% or more, particularly preferably 2 mass% or more, and preferably 20 mass% or less, more preferably 10 mass% or less, particularly preferably 6 mass% or less, based on 100 mass% of the resin component of the magnetic paste. When the amount of the (D) dispersant is within the above range, the viscosity of the magnetic paste can be reduced. In addition, it is usually possible to effectively suppress the viscosity change during the continuation of the magnetic paste, and to effectively improve the magnetic properties of the cured product.

[0088] <(E) Optional Additives> The magnetic paste according to one embodiment of the present invention may further contain an optional additive (E) in combination with the above-mentioned components (A) to (D). The optional additive (E) as the component (E) does not include those corresponding to the above-mentioned components (A) to (D).

[0089] (E) Examples of optional additives include thermoplastic resins such as phenoxy resins, polyimide resins, polyvinyl acetal resins, polyolefin resins, polybutadiene resins, polyamideimide resins, polyetherimide resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polycarbonate resins, polyether ether ketone resins, and polyester resins; radical polymerizable compounds such as maleimide-based radical polymerizable compounds, vinylphenyl-based radical polymerizable compounds, (meth)acrylic-based radical polymerizable compounds, allyl-based radical polymerizable compounds, and polybutadiene-based radical polymerizable compounds; radical polymerization initiators such as peroxide-based radical polymerization initiators and azo-based radical polymerization initiators; inorganic fillers such as silica particles; organic fillers such as rubber particles; organometallic compounds such as organocopper compounds and organozinc compounds; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentone and montmorillonite; defoamers such as silicone-based defoamers, acrylic-based defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; adhesion improvers such as urea silane; adhesion imparters such as triazole-based adhesion imparters, tetrazole-based adhesion imparters, and triazine-based adhesion imparters; antioxidants such as hindered phenol-based antioxidants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, and red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); and stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers. (E) The optional additives may be used alone or in combination of two or more kinds.

[0090] <Moisture content of magnetic paste> The magnetic paste according to one embodiment of the present invention may contain water as a volatile component in combination with the non-volatile components (A) to (E) described above. However, the moisture content of the magnetic paste according to this embodiment is in a small specific range. Therefore, the magnetic paste according to this embodiment may contain water or may not contain water, but the amount of water is usually small and preferably does not contain water.

[0091] The specific range of the moisture content of the magnetic paste is usually 1000 ppm or less, preferably 950 ppm or less, and more preferably 900 ppm or less. When the moisture content of the magnetic paste is low in this way, the magnetic paste can reduce viscosity change during use while containing magnetic powder with a small particle size. The lower limit of the moisture content is ideally 0 ppm, but may be 100 ppm or more, 200 ppm or more, or 300 ppm or more from the viewpoint of easy production of the magnetic paste. The moisture content of the magnetic paste can be measured at 25°C by the Karl Fischer method. The specific measurement conditions can be the method described in the examples.

[0092] The moisture content of the magnetic paste [ppm] is C W (A) The average particle size of the magnetic powder [μm] is D A The mass ratio [mass%] of (A) magnetic powder to 100 mass% of the non-volatile components of the magnetic paste is C M Let us assume that. In this case, the ratio "C W / C M " is preferably 11.5 or less, more preferably 11.0 or less, and particularly preferably 10.5 or less. There is no particular lower limit, and it may be 0.0 or more, 0.1 or more, 0.2 or more, etc. W / C M " corresponds to the amount of moisture per mass of (A) magnetic powder. W / C M When " is in the above range, the change in viscosity of the magnetic paste during application can be effectively reduced. Also, the parameter "CW / (D A 2 ×C M ) is preferably 1.25 or less, more preferably 1.20 or less, and particularly preferably 1.15 or less. There is no particular lower limit, and it may be 0.00 or more, 0.01 or more, 0.02 or more, etc. W / (D A 2 ×C M ) is correlated with the amount of moisture per surface area of ​​the (A) magnetic powder when the (A) magnetic powder is assumed to be spherical. W / (D A 2 ×C M When "(t)" is in the above range, the change in viscosity of the magnetic paste when it is applied can be effectively reduced.

[0093] <(F) Organic solvent> The magnetic paste according to one embodiment of the present invention may further contain (F) an organic solvent as a volatile component in addition to the non-volatile components (A) to (E) described above.

[0094] (F) Examples of organic solvents include ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, and diphenyl ether; alcohol-based solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, and methyl methoxypropionate. Examples of the organic solvent include ether ester solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butyl carbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. (F) The organic solvent may be used alone or in combination of two or more.

[0095] The amount of organic solvent contained in the magnetic paste is preferably less than 1.0% by mass, more preferably 0.8% by mass or less, even more preferably 0.5% by mass or less, and particularly preferably 0.1% by mass or less, based on the total mass of the magnetic paste. The lower limit may be, for example, 0.001% by mass or more, but 0% by mass is preferable. That is, it is preferable that the magnetic paste does not contain organic solvent. In particular, the amount of organic solvent having a boiling point of usually 150°C or less, preferably 140°C or less, and more preferably 130°C or less is preferably within the above range. When the amount of organic solvent in the magnetic paste is small, the viscosity change due to the volatilization of the organic solvent can be suppressed, so that the viscosity change during the continuation of the magnetic paste can be effectively reduced. Furthermore, it is usually possible to suppress the generation of voids due to the volatilization of the organic solvent during thermal curing of the magnetic paste.

[0096] <Magnetic paste manufacturing method> The magnetic paste can be produced, for example, by a method including a step (i) of mixing materials for the magnetic paste to obtain a paste-like composition, and a step (ii) of drying the paste-like composition to obtain the magnetic paste.

[0097] In step (i), (A) magnetic powder and (B) thermosetting resin, as well as optional components such as (C) hardening accelerator, (D) dispersant, (E) optional additive, and (F) organic solvent, are mixed to obtain a paste-like composition. The magnetic paste materials such as components (A) to (F) may be mixed partially or entirely at the same time, or may be mixed sequentially. Mixing may be performed at room temperature, or the temperature may be appropriately set during the process of mixing each material. Therefore, heating and / or cooling may be performed temporarily or throughout the mixing process. Furthermore, stirring or shaking may be performed during the process of mixing each material.

[0098] In step (ii), the paste-like composition is dried to obtain the magnetic paste according to the present embodiment. The paste-like composition prepared in step (i) may contain moisture due to the infiltration of moisture from the air. In step (ii), this moisture is removed to obtain a magnetic paste having a moisture content within the specific range described above.

[0099] The drying of the paste-like composition is preferably carried out by vacuum drying. In vacuum drying, the paste-like composition is usually placed in a container under reduced pressure to remove moisture from the paste-like composition. When performing vacuum drying, the absolute pressure in the container is usually 800 Pa or less, preferably 750 Pa or less, more preferably 600 Pa or less, and particularly preferably 400 Pa or less. The lower limit is ideally 0 Pa, but may be 100 Pa or more, 200 Pa or more, etc. When drying is performed under such a high vacuum, moisture can be smoothly removed from the paste-like composition, so that the magnetic paste can be produced in a short time.

[0100] The drying of the paste-like composition is preferably carried out at room temperature or in a cooled environment. The specific drying temperature of the paste-like composition is preferably 30° C. or less, more preferably 25° C. or less, and particularly preferably 20° C. or less. There is no particular lower limit, and it may be 5° C. or more, 10° C. or more, 15° C. or more, etc. When the drying temperature is within the above range, the progress of the curing reaction of the (B) thermosetting resin can be suppressed, and therefore the viscosity of the magnetic paste produced can be reduced.

[0101] The drying time of the paste composition can be appropriately set within a range that allows a magnetic paste having a moisture content within the above-mentioned range to be obtained. The specific drying time is preferably 10 minutes or more, more preferably 20 minutes or more, particularly preferably 30 minutes or more, and is preferably 24 hours or less, more preferably 12 hours or less, and more preferably 6 hours or less.

[0102] <Characteristics of magnetic paste> The magnetic paste according to this embodiment can reduce the change in viscosity over time. Specifically, the viscosity increase rate of the magnetic paste over time can be reduced. For example, the viscosity increase rate of the magnetic paste when left for one week in an environment with a temperature of 25°C and a relative humidity of 60% can be preferably less than 1.7, more preferably less than 1.6, and particularly preferably less than 1.5. The lower limit is usually 1.0 or more, and may be 1.1 or more, 1.2 or more, etc. The viscosity increase rate can be measured by the method described in the examples.

[0103] The magnetic paste according to the present embodiment preferably has a low viscosity. The viscosity of the magnetic paste at 25°C is preferably 300 Pa·s or less, more preferably 250 Pa·s or less, even more preferably 200 Pa·s or less, and preferably 10 Pa·s or more, preferably 20 Pa·s or more, more preferably 30 Pa·s or more. When the viscosity of the magnetic paste is equal to or less than the upper limit, the magnetic paste can smoothly enter the holes formed in the core substrate. When the viscosity of the magnetic paste is equal to or more than the lower limit, the magnetic paste can be prevented from flowing out of the through holes penetrating the core substrate. Therefore, when the viscosity of the magnetic paste is within the above range, the magnetic paste can be well filled into the holes. The viscosity of the magnetic paste can be measured, for example, using an E-type viscometer (Toki Sangyo Co., Ltd. "RE-80U", 3°×R9.7 cone, rotation speed 5 rpm), and in detail, can be measured by the method described in the examples described later.

[0104] The above-mentioned magnetic paste can be cured by heat. Therefore, by thermally curing the magnetic paste, a cured product of the magnetic paste can be obtained. Normally, among the components contained in the magnetic paste, volatile components such as water and (F) organic solvent can be volatilized by the heat during thermal curing, but non-volatile components such as components (A) to (E) do not volatilize by the heat during thermal curing. Therefore, the cured product of the magnetic paste can contain the non-volatile components of the magnetic paste or their reaction products.

[0105] The cured product of the magnetic paste can have excellent magnetic properties. For example, the relative permeability of the cured product of the magnetic paste measured under the measurement conditions of a measurement frequency of 50 MHz and a measurement temperature of 25°C is preferably 4 or more, more preferably 6 or more, even more preferably 8 or more, and particularly preferably 10 or more. There is no particular upper limit, and it can be, for example, 40 or less. The relative permeability can be measured, for example, by using a cured product obtained by heating the magnetic paste at 190°C for 90 minutes, using a method described in the examples below.

[0106] For example, the magnetic loss of the cured product of the magnetic paste measured under conditions of a measurement frequency of 50 MHz and a measurement temperature of 25° C. is preferably 0.10 or less, more preferably 0.08 or less, even more preferably 0.06 or less, and particularly preferably 0.05 or less. The lower limit is ideally 0.00 or more, but is usually 0.001 or more. The magnetic loss can be measured, for example, by using a cured product obtained by heating the magnetic paste at 190° C. for 90 minutes, using the method described in the examples below.

[0107] From the viewpoint of utilizing the above-mentioned advantages, the magnetic paste is preferably used as a paste for filling holes in a core substrate. For example, the magnetic paste is introduced into a hole, and the hole is filled with the magnetic paste. Then, the magnetic paste is hardened to form a magnetic layer in the hole. In particular, the magnetic paste of this embodiment can be suitably used as a magnetic paste for filling through holes penetrating a core substrate (i.e., a magnetic paste for filling through holes).

[0108] <Circuit board> A circuit board according to an embodiment of the present invention includes the hardened magnetic paste described above. The specific structure of the circuit board is not limited as long as it includes the hardened magnetic paste. An example of this circuit board is a circuit board including a core substrate having holes formed therein and a magnetic layer filled in the holes. In the circuit board according to this example, the magnetic layer includes the hardened magnetic paste, and preferably includes only the hardened magnetic paste.

[0109] The circuit board according to the above example is, for example, (1) filling holes in a core substrate with a magnetic paste; (2) hardening the magnetic paste filled in the holes to form a magnetic layer; The present invention can be produced by a production method including the steps of: (3) polishing the surface of the magnetic layer or magnetic paste; (4) roughening the magnetic layer; and (5) forming a conductor layer on the surface of the magnetic layer; The above steps (1) to (5) are usually carried out in this order, but step (2) may be carried out after step (3). In the following explanation, an example will be given in which a core substrate having a through hole formed therein as a hole penetrating the core substrate in the thickness direction is used.

[0110] <Process (1)> Step (1) usually includes a step of preparing a core substrate having a through hole formed therein. The core substrate may be prepared by purchasing it from the market. Alternatively, the core substrate may be prepared by manufacturing it using an appropriate material. An example of a method for manufacturing the core substrate will be described below.

[0111] Fig. 1 is a cross-sectional view showing a core substrate 10 before through holes are formed in a method for manufacturing a circuit board according to one embodiment of the present invention. The step of preparing the core substrate 10 may include a step of preparing a core substrate 10 in which no through holes to be filled with a magnetic layer are formed, as in the example shown in Fig. 1. This core substrate 10 is a substrate before through holes are formed, and may be a plate-shaped member.

[0112] The core substrate 10 usually includes a support substrate 11. Examples of the support substrate 11 include insulating substrates such as a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. A metal layer may be provided on the support substrate 11. The metal layer may be provided on one side or both sides of the support substrate 11. Here, an example is shown in which metal layers 12 and 13 are provided on both surfaces of the support substrate 11. Examples of the metal layers 12 and 13 include layers formed of a metal such as copper. The metal layers 12 and 13 may be, for example, copper foil such as a copper foil with a carrier, or may be metal layers formed of a material for the conductor layer described later.

[0113] FIG. 2 is a cross-sectional view showing a core substrate 10 having a through hole 14 formed therein in a method for manufacturing a circuit board according to an embodiment of the present invention. The step of preparing the core substrate 10 may include a step of forming a through hole 14 in the core substrate 10, as in the example shown in FIG. 2. The diameter of the through hole is not particularly limited and may be, for example, 200 μm to 800 μm. The through hole 14 can be formed by, for example, drilling, laser irradiation, plasma irradiation, or the like. Usually, the through hole 14 can be formed by forming a through hole in the core substrate 10. As a specific example, the through hole 14 can be formed by using a commercially available drilling device. An example of a commercially available drilling device is "ND-1S211" manufactured by Hitachi Via Mechanics Co., Ltd.

[0114] FIG. 3 is a cross-sectional view showing a core substrate 10 having a plating layer 20 formed in a through hole 14 in a method for manufacturing a circuit board according to an embodiment of the present invention. The step of preparing the core substrate 10 may include a step of forming a plating layer 20 as shown in FIG. 3 after subjecting the core substrate 10 to a roughening treatment as necessary. The roughening treatment may be either a dry or wet roughening treatment. An example of the dry roughening treatment is a plasma treatment. An example of the wet roughening treatment is a method in which a swelling treatment using a swelling liquid, a roughening treatment using an oxidizing agent, and a neutralization treatment using a neutralizing liquid are performed in this order. The plating layer 20 may be formed by a plating method. The procedure for forming the plating layer 20 by a plating method may be the same as the formation of a conductor layer in step (5) described later. Here, an example in which the plating layer 20 is formed in the through hole 14, on the surface of the metal layer 12, and on the surface of the metal layer 13 will be described. In addition, in this example, the core substrate provided with the plating layer 20 will be described by assigning the same reference numeral "10" as the core substrate 10 before the plating layer 20 is formed.

[0115] FIG. 4 is a cross-sectional view showing a state where the through-holes of the core substrate 10 are filled with the magnetic paste 30a in the manufacturing method of the circuit board according to one embodiment of the present invention. Step (1) includes filling the through-holes 14 of the core substrate 10 with the magnetic paste 30a as shown in FIG. 4 after preparing the core substrate 10 in which the through-holes 14 are formed as described above. The filling can be performed by, for example, a printing method. Examples of the printing method include a method of printing the magnetic paste 30a into the through-holes 14 using a squeegee, a method of printing the magnetic paste 30a using a cartridge, a method of printing the magnetic paste 30a by mask printing, a roll coating method, an inkjet method, and the like. Among them, a mask printing method including mask printing is preferred, and a screen printing method using a screen mask having a mask portion that does not allow the magnetic paste to pass and a mesh portion that allows the magnetic paste to pass is particularly preferred.

[0116] It is preferable that the through-holes 14 are filled with the magnetic paste in a reduced pressure environment. The specific pressure during filling is preferably 1000 Pa or less, more preferably 500 Pa or less, and particularly preferably 300 Pa or less. There is no particular lower limit, and it can be, for example, 0 Pa or more, 10 Pa or more, 20 Pa or more, etc. When filling the magnetic paste in a reduced pressure environment, it is possible to suppress the formation of voids in the filled magnetic paste.

[0117] When the magnetic paste 30a is filled, the excess magnetic paste 30a usually protrudes or adheres to the outside of the through-hole 14a. Therefore, the magnetic paste 30a may be provided not only inside the through-hole 14a but also outside the through-hole 14a.

[0118] <Process (2)> Fig. 5 is a schematic cross-sectional view for explaining step (2) of the method for manufacturing a circuit board according to one embodiment of the present invention. Step (2) includes filling the through-holes 14 with magnetic paste 30a and then curing the magnetic paste 30a, as shown in Fig. 5. By curing the magnetic paste 30a, a magnetic layer 30 including a cured product of the magnetic paste 30a can be formed in the through-holes 14.

[0119] The magnetic paste 30a is usually hardened by thermal hardening. The thermal hardening conditions of the magnetic paste 30a can be appropriately set within a range in which the hardening of the magnetic paste 30a proceeds. The hardening temperature is preferably 120°C or higher, more preferably 130°C or higher, and even more preferably 150°C or higher, and is preferably 245°C or lower, more preferably 220°C or lower, and even more preferably 200°C or lower. The hardening time is preferably 5 minutes or higher, more preferably 10 minutes or higher, and even more preferably 15 minutes or higher, and is preferably 120 minutes or lower, more preferably 110 minutes or lower, and even more preferably 100 minutes or lower.

[0120] The degree of hardness of the hardened product of the magnetic paste 30a obtained in step (2) is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The degree of hardness can be measured, for example, by using a differential scanning calorimeter.

[0121] The method for manufacturing the circuit board may include a step (preheating step) of heating the magnetic paste 30a at a temperature lower than the curing temperature after filling the through-holes 14 with the magnetic paste 30a and before curing the magnetic paste 30a. For example, prior to curing the magnetic paste 30a, the magnetic paste 30a may be preheated at a temperature of typically 50° C. or higher and lower than 120° C. (preferably 60° C. or higher and 110° C. or lower, more preferably 70° C. or higher and 100° C. or lower) for typically 5 minutes or longer (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes).

[0122] <Process (3)> Fig. 6 is a schematic cross-sectional view for explaining step (3) of the method for manufacturing a circuit board according to one embodiment of the present invention. Step (3) includes polishing excess magnetic layer 30 protruding from or attached to core substrate 10, as shown in Fig. 6. Since the excess magnetic layer 30 is removed by polishing, the surface of magnetic layer 30 can be flattened.

[0123] The polishing method may be a method capable of removing the excess magnetic layer 30 protruding from or adhering to the core substrate 10. Examples of such polishing methods include buff polishing, belt polishing, ceramic polishing, etc. Examples of commercially available buff polishing devices include "NT-700IM" manufactured by Ishii Hyoki Co., Ltd.

[0124] The arithmetic mean roughness (Ra) of the polished surface of the magnetic layer 30 (after the cured layer is thermally cured) is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with the conductor layer. The upper limit is preferably 1000 nm or less, more preferably 900 nm or less, and even more preferably 800 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.

[0125] When step (3) is performed after step (2), the magnetic layer 30 may be subjected to a heat treatment after step (2) and before step (3) in order to further increase the degree of hardening of the hardened material contained in the magnetic layer 30. The temperature in the heat treatment may be similar to the above-mentioned hardening temperature. The specific heat treatment temperature is preferably 120°C or higher, more preferably 130°C or higher, and even more preferably 150°C or higher, and preferably 245°C or lower, more preferably 220°C or lower, and even more preferably 200°C or lower. The heat treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 15 minutes or more, and preferably 90 minutes or less, more preferably 70 minutes or less, and even more preferably 60 minutes or less.

[0126] When step (3) is performed before step (2), a preheating treatment may be performed before step (3) to heat the magnetic paste at a temperature lower than the hardening temperature of the magnetic paste. The temperature in the preheating treatment is preferably 100° C. or higher, more preferably 110° C. or higher, and even more preferably 120° C. or higher, and preferably 245° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The heat treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 15 minutes or more, and preferably 90 minutes or less, more preferably 70 minutes or less, and even more preferably 60 minutes or less.

[0127] <Process (4)> Step (4) includes subjecting the magnetic layer 30 to a roughening treatment (desmear treatment). Typically, the roughening treatment is applied to the polished surface of the magnetic layer. In step (4), the roughening treatment may be applied not only to the polished surface of the magnetic layer but also to the surface of the core substrate 10.

[0128] The procedure and conditions of the roughening step are not particularly limited, and may be, for example, the procedure and conditions used in the manufacturing method of a multilayer printed wiring board. As a specific example, the roughening treatment may be performed by a method including, in this order, a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid.

[0129] Examples of the swelling liquid used in the swelling step include an alkaline solution, a surfactant solution, and the like, and an alkaline solution is preferred. As the alkaline solution that is the swelling liquid, a sodium hydroxide solution and a potassium hydroxide solution are more preferred. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan.

[0130] The swelling treatment using a swelling liquid can be carried out, for example, by immersing the magnetic layer 30 for 1 to 20 minutes in a swelling liquid at 30° C. to 90° C. From the viewpoint of suppressing swelling of the resin constituting the magnetic layer 30 to an appropriate level, it is preferable to immerse the magnetic layer 30 in a swelling liquid at 40° C. to 80° C. for 5 to 15 minutes.

[0131] An example of an oxidizing agent used in the roughening treatment is an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably carried out by immersing the magnetic layer 30 in a solution of the oxidizing agent heated to 60°C to 80°C for 10 to 30 minutes. The concentration of the permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact P" and "Dosing Solution Securigans P" manufactured by Atotech Japan.

[0132] The neutralizing liquid that can be used for the neutralization treatment is preferably an acidic aqueous solution. An example of a commercially available neutralizing liquid is "Reduction Solution Securigans P" manufactured by Atotech Japan. The neutralization treatment using the neutralizing liquid can be performed by immersing the treated surface that has been roughened with an oxidizing solution in the neutralizing liquid at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, a method of immersing the magnetic layer 30 that has been roughened with an oxidizing solution in the neutralizing liquid at 40°C to 70°C for 5 to 20 minutes is preferable.

[0133] The arithmetic mean roughness (Ra) of the surface of the magnetic layer 30 after roughening treatment is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with the conductor layer. The upper limit is preferably 1500 nm or less, more preferably 1200 nm or less, and even more preferably 1000 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.

[0134] <Process (5)> FIG. 7 is a schematic cross-sectional view for explaining step (5) of the method for manufacturing a circuit board according to an embodiment of the present invention. Step (5) includes forming a conductor layer 40 on the surface of the magnetic layer 30, as shown in FIG. 7. When the method for manufacturing a circuit board includes step (3), step (5) usually includes forming a conductor layer 40 on the polished surface of the magnetic layer 30. When the method for manufacturing a circuit board includes step (4), step (5) usually includes forming a conductor layer 40 on the roughened surface of the magnetic layer 30. In this embodiment, an example is shown in which the conductor layer 40 is formed not only on the surface of the magnetic layer 30 but also on the surrounding surfaces (for example, the surface of the core substrate 10 and the surface of the plating layer 20). Also, FIG. 7 shows an example in which the conductor layer 40 is formed on both sides of the core substrate 10, but the conductor layer 40 may be formed only on one side of the core substrate 10.

[0135] Fig. 8 is a schematic cross-sectional view for explaining step (5) of the method for producing a circuit board according to one embodiment of the present invention. As shown in Fig. 8, step (5) may include forming a conductor layer 40, and then removing parts of the conductor layer 40, the first metal layer 12, the second metal layer 13, and the plating layer 20 by a process such as etching to form a pattern conductor layer 41.

[0136] The conductor layer 40 can be formed by, for example, plating, sputtering, vapor deposition, etc., among which plating is preferred. In a preferred embodiment, the surface of the magnetic layer 30 (and, if necessary, the core substrate 10) can be plated by an appropriate method such as a semi-additive method or a full-additive method to form a patterned conductor layer 41 having a desired wiring pattern. Examples of materials for the conductor layer 40 include single metals such as gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium; and alloys of two or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. Among these, from the viewpoints of versatility, cost, ease of patterning, and the like, it is preferable to use chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy, it is more preferable to use chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or a nickel-chromium alloy, and it is even more preferable to use copper.

[0137] Here, an example of a method for forming the patterned conductor layer 41 will be described in detail. A plating seed layer is formed on the surface of the magnetic layer 30 by electroless plating. Next, a mask pattern is formed on the formed plating seed layer as necessary, and then an electrolytic plating layer is formed by electrolytic plating. Thereafter, the mask pattern is removed as necessary, and unnecessary plating seed layer is further removed by a process such as etching, to form the patterned conductor layer 41 having a desired wiring pattern. After the formation of the patterned conductor layer 41, an annealing treatment may be performed as necessary to improve the adhesion strength of the patterned conductor layer 41. The annealing treatment can be performed, for example, by heating at 150°C to 200°C for 20 minutes to 90 minutes.

[0138] From the viewpoint of thinning, the thickness of the patterned conductor layer 41 is preferably 70 μm or less, more preferably 60 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, particularly preferably 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less. The lower limit is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more.

[0139] By the above method, a circuit board 1 having a magnetic layer 30 containing a hardened product of the magnetic paste is obtained. The magnetic layer 30 is obtained by hardening the magnetic paste 30a, and therefore contains the hardened product of the magnetic paste 30a. Therefore, the magnetic layer 30 can contain a large amount of small particle size (A) magnetic powder, and can have excellent magnetic properties. In addition, the magnetic paste 30a, which is the material of the magnetic layer 30, can suppress viscosity changes during use while containing small particle size (A) magnetic powder. Therefore, the frequency of adjusting the filling conditions of the magnetic paste 30a into the through holes 14 in step (1) can be reduced, and the circuit board 1 can be manufactured efficiently.

[0140] <Inductor board> An inductor component according to an embodiment of the present invention includes the circuit board described above. Such an inductor component typically has an inductor pattern formed of a conductor around at least a portion of the magnetic layer. For example, the inductor component described in JP 2016-197624 A can be used.

[0141] The inductor component can be used as a wiring board for mounting electronic components such as semiconductor chips, and can also be used as a (multilayer) printed wiring board using such a wiring board as an inner layer substrate. Also, such a wiring board can be used as an individual chip inductor component, and can also be used as a printed wiring board with the chip inductor component surface mounted.

[0142] In addition, various types of semiconductor devices can be manufactured using such a wiring board. The semiconductor devices including such wiring boards can be suitably used in electric products (e.g., computers, mobile phones, digital cameras, televisions, etc.) and vehicles (e.g., motorcycles, automobiles, trains, ships, aircraft, etc.). EXAMPLES

[0143] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. In the following description, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Furthermore, unless otherwise specified, the operations shown below were performed at room temperature and normal pressure (25°C and 1 atm). Furthermore, the volume content (volume %) was calculated using the mass and specific gravity.

[0144] <Example 1: Preparation of magnetic paste 1> Epoxy resin ("ZX-1059", a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin, epoxy equivalent of approximately 165 g / eq., manufactured by Nippon Steel Chemical & Material Co., Ltd.) 15 parts by mass, epoxy resin ("ZX-1658GS", cyclic aliphatic diglycidyl ether, reactive diluent, epoxy equivalent of 135 g / eq., manufactured by Nippon Steel Chemical & Material Co., Ltd.) 5 parts by mass, dispersant ("C-2093I", acidic dispersant for nanoparticles, manufactured by NOF Corporation) 1.1 parts by mass, hardening accelerator ("2MZA-PW", imidazole-based epoxy resin hardening accelerator, manufactured by Shikoku Kasei Co., Ltd.) 1 part by mass, and magnetic powder ("AW2-08 PF3F", Fe-Cr-Si alloy (amorphous), average particle size 3.0 μm, specific surface area 0.66 m 2 / g, specific gravity 7.11g / cm 3 The mixture was stirred at 2000 rpm for 1 minute using a stirrer (Awatori Rentaro ARE-310, manufactured by Thinky Corporation) to obtain a paste-like composition.

[0145] A vacuum desiccator (Vacuum Desiccator VM, manufactured by AS ONE Corporation) was prepared, and an absolute pressure gauge (Digital Vacuum Gauge Pilot PLUS, manufactured by Asada Corporation) was used to confirm that the absolute pressure inside the vacuum desiccator was 350 Pa. The paste-like composition was vacuum-dried in this vacuum desiccator for 60 minutes to prepare magnetic paste 1.

[0146] <Example 2: Preparation of magnetic paste 2> Instead of 1.1 parts by mass of the dispersant ("C-2093I", an acidic dispersant for nanoparticles, manufactured by NOF Corporation), 1.1 parts by mass of a dispersant ("DA-375", a polyether phosphate ester, manufactured by Kusumoto Chemicals Co., Ltd.) was used. In addition, magnetic powder ("AW2-08 PF3F", Fe-Cr-Si alloy (amorphous), average particle size 3.0 μm, specific surface area 0.66 m 2 / g, specific gravity 7.11g / cm 3 Instead of 180 parts by mass of magnetic powder ("MA-RCO-5", Fe-Ni alloy, average particle size 3.0 μm, specific surface area 0.45 m, manufactured by Epson Atmix), 2 / g, specific gravity 8.0g / cm 3 A magnetic paste 2 was prepared in the same manner as in Example 1 except for the above points.

[0147] <Example 3: Preparation of magnetic paste 3> Instead of 1.1 parts by mass of a dispersant ("C-2093I", an acidic dispersant for nanoparticles, manufactured by NOF Corporation), 1.1 parts by mass of a dispersant ("SC-1015F", a multifunctional comb-type functional polymer having a polyoxyalkylene chain, manufactured by NOF Corporation) was used. In addition, a magnetic powder ("AW2-08 PF3F", an Fe-Cr-Si alloy (amorphous), average particle size 3.0 μm, specific surface area 0.66 m) was used. 2 / g, specific gravity 7.11g / cm 3 , manufactured by Epson Atmix) instead of 180 parts by mass of magnetic powder ("M05S", Fe-Mn ferrite, average particle size 3.0 μm, specific surface area 0.68 m 2 / g, specific gravity 5.1g / cm 3 A magnetic paste 3 was prepared in the same manner as in Example 1 except for the above points.

[0148] <Example 4: Preparation of magnetic paste 4> Instead of 1.1 parts by mass of the dispersant ("C-2093I", an acidic dispersant for nanoparticles, manufactured by NOF Corporation), 1.1 parts by mass of a dispersant ("PB881", a polyamine-based dispersant, manufactured by Ajinomoto Fine-Techno Co., Ltd.) was used. In addition, magnetic powder ("AW2-08 PF3F", Fe-Cr-Si-based alloy (amorphous), average particle size 3.0 μm, specific surface area 0.66 m) was used. 2 / g, specific gravity 7.11g / cm 3 , manufactured by Epson Atmix) instead of 180 parts by mass of magnetic powder ("MZ05S", Fe-Mn-Zn ferrite, average particle size 3.0 μm, specific surface area 0.58 m 2 / g, specific gravity 5.1g / cm 3 A magnetic paste 4 was prepared in the same manner as in Example 1 except for the above points.

[0149] <Example 5: Preparation of magnetic paste 5> Magnetic paste 5 was prepared in the same manner as in Example 4, except that the absolute pressure in the vacuum desiccator was changed from 350 Pa to 750 Pa.

[0150] <Example 6: Preparation of magnetic paste 6> Magnetic paste 6 was prepared in the same manner as in Example 4, except that 1.1 parts by mass of the dispersant ("PB881", polyamine-based dispersant, manufactured by Ajinomoto Fine-Techno Co., Ltd.) was not used.

[0151] <Comparative Example 1: Preparation of Magnetic Paste 7> Epoxy resin ("ZX-1059", a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin, epoxy equivalent of approximately 165 g / eq., manufactured by Nippon Steel Chemical & Material Co., Ltd.) 15 parts by mass, epoxy resin ("ZX-1658GS", cyclic aliphatic diglycidyl ether, reactive diluent, epoxy equivalent of 135 g / eq., manufactured by Nippon Steel Chemical & Material Co., Ltd.) 5 parts by mass, dispersant ("SC-1015F", acidic dispersant for nanoparticles, manufactured by NOF Corporation) 1.1 parts by mass, curing accelerator ("2MZA-PW", imidazole-based epoxy resin curing accelerator, manufactured by Shikoku Kasei Co., Ltd.) 1 part by mass, and magnetic powder ("M05S", Fe-Mn-based ferrite, average particle size 3 μm, specific surface area 0.68 m 2 / g, specific gravity 5.1g / cm 3 The mixture was stirred at 2000 rpm for 1 minute using a stirrer (Awatori Rentaro ARE-310, manufactured by Thinky Corporation) to obtain a paste-like composition.

[0152] A vacuum desiccator (Vacuum Desiccator VM, manufactured by AS ONE Corporation) was prepared, and an absolute pressure gauge (Digital Vacuum Gauge Pilot PLUS, manufactured by Asada Corporation) was used to confirm that the absolute pressure inside the vacuum desiccator was 4000 Pa. The paste-like composition was vacuum-dried in this vacuum desiccator for 60 minutes to prepare magnetic paste 7.

[0153] <Comparative Example 2: Preparation of Magnetic Paste 8> Instead of 1.1 parts by mass of a dispersant ("SC-1015F", a multifunctional comb-type functional polymer having a polyoxyalkylene chain, manufactured by NOF Corporation), 1.1 parts by mass of a dispersant ("PB881", a polyamine-based dispersant, manufactured by Ajinomoto Fine-Techno Co., Ltd.) was used. In addition, a magnetic powder ("M05S", an Fe-Mn-based ferrite, with an average particle size of 3.0 μm and a specific surface area of ​​0.68 m) was used. 2 / g, specific gravity 5.1g / cm 3 , manufactured by Powder Tech Co., Ltd.) 110 parts by mass, instead of magnetic powder ("MZ05S", Fe-Mn-Zn ferrite, average particle size 3.0 μm, specific surface area 0.58 m 2 / g, specific gravity 5.1g / cm 3A magnetic paste 8 was prepared in the same manner as in Comparative Example 1, except for the above points.

[0154] <Measurement of moisture content of magnetic paste> 2.5g to 3.0g of magnetic paste was taken out, and the moisture content of the magnetic paste was measured using a Karl Fischer moisture measuring device ("CA-200 trace moisture measuring device" manufactured by Mitsubishi Chemical Analytech Co., Ltd.) using the coulometric titration method. This device is composed of a glass container capable of storing and heating the sample, and a titration device containing a reaction solution for titrating the moisture vaporized when the sample is heated. The vaporized moisture is transferred from the glass container to the reaction solution in the titration device by flowing nitrogen at a flow rate of 250±25ml / min. The sample was placed in a glass container substituted with a nitrogen atmosphere (water vapor amount <0.1ppm), and the amount of vaporized moisture was measured under conditions of 130°C to calculate the moisture content (initial moisture content) of the magnetic paste.

[0155] <Measurement of initial viscosity of magnetic paste> The temperature of the magnetic paste was kept at 25±2°C, and the viscosity (initial viscosity) η0 at 25°C was measured using an E-type viscometer (Toki Sangyo Co., Ltd. "RE-80U", 3°×R9.7 cone, rotation speed 5 rpm).

[0156] <Measurement of viscosity of magnetic paste after 7 days> The magnetic paste was left for one week in an environment with a relative humidity of 60% while maintaining the temperature of the magnetic paste at 25±2°C. After that, the viscosity (post-storage viscosity) η7 of the magnetic paste at 25°C was measured using an E-type viscometer (Toki Sangyo Co., Ltd. "RE-80U", 3°×R9.7 cone, 5 rpm).

[0157] <Calculation of viscosity increase rate> The viscosity of the magnetic paste after 7 days was divided by the initial viscosity (η0) to calculate the viscosity increase rate (η7 / η0). Based on the calculated viscosity increase rate, the storage stability of the magnetic paste was evaluated according to the following criteria from the viewpoint of printability stability. ○: Viscosity increase rate is less than 1.7. ×: Viscosity increase rate is 1.7 or more.

[0158] <Method of measuring magnetic properties> As a support, a polyethylene terephthalate (PET) film ("PET501010" manufactured by Lintec Corporation, thickness 50 μm) having a release surface treated with a silicone release agent was prepared. The magnetic paste was uniformly applied to the release surface of the PET film with a doctor blade. The magnetic paste was then cured by heating at 190°C for 90 minutes to obtain a sheet-like cured product. After peeling off the support, the cured product was cut to obtain an evaluation sample with a width of 5 mm and a length of 18 mm. The relative permeability (μ') and magnetic loss (μ'') of this evaluation sample were measured using an Agilent Technologies ("HP8362B" manufactured by Agilent Technologies) by a 3-turn coil method at a measurement frequency of 50 MHz and 25°C. The magnetic loss was calculated by the formula "tan δ=μ'' / μ'".

[0159] <Results of Examples and Comparative Examples> The results of the examples and comparative examples are shown in the table below.

[0160] [Table 1]

[0161] [Table 2]

[0162] <Reference Example 1: Preparation of Magnetic Paste 9> 15 parts by mass of epoxy resin ("ZX-1059", a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin, manufactured by Nippon Steel Chemical & Material Co., Ltd.), 5 parts by mass of epoxy resin ("ZX-1658GS", cyclic aliphatic diglycidyl ether, manufactured by Nippon Steel Chemical & Material Co., Ltd.), 1.1 parts by mass of dispersant ("C-2093I", an acidic dispersant for nanoparticles, manufactured by NOF Corporation), 1 part by mass of curing accelerator ("2MZA-PW", an imidazole-based epoxy resin curing accelerator, manufactured by Shikoku Kasei Co., Ltd.), and 110 parts by mass of magnetic powder ("M05S", Fe-Mn-based ferrite, average particle size 3 μm, manufactured by Powdertech Co., Ltd.) were mixed and stirred at 2000 rpm for 1 minute using a stirrer (Awatori Rentaro ARE-310, manufactured by Thinky Corporation) to prepare magnetic paste 9.

[0163] <Reference Example 2: Preparation of magnetic paste 10> A magnetic paste 10 was prepared in the same manner as in Reference Example 1, except that 110 parts by mass of magnetic powder ("M05S", Fe-Mn ferrite, average particle size 3.0 μm, manufactured by Powder Tech Co., Ltd.) was used instead of 110 parts by mass of magnetic powder ("M05S 50 μm", Fe-Mn ferrite, average particle size 50.0 μm, manufactured by Powder Tech Co., Ltd.).

[0164] <Reference example results> The magnetic pastes obtained in Reference Examples 1 and 2 were evaluated by the methods described above. The results of the Reference Examples are shown in the table below.

[0165] [Table 3]

[0166] <Consideration> From the results of Reference Example 1, it was confirmed that the magnetic paste containing magnetic powder having an average particle size of 10 μm or less has a large increase in viscosity during use. Also, from the results of Reference Example 2, it was confirmed that the magnetic paste containing magnetic powder having an average particle size of more than 10 μm has a small increase in viscosity during use. The magnetic paste of Reference Example 1 and the magnetic paste of Reference Example 2 have the same composition except for the average particle size of the magnetic powder. Therefore, from the comparison between Reference Examples 1 and 2, it was confirmed that the problem of viscosity increase during use occurs specifically when magnetic powder having a small average particle size is used for the high performance of inductor components in recent years. [Explanation of symbols]

[0167] 1 Circuit Board 10 Core Board 11 Support substrate 12 metal layer 13 Metal layer 14 through hole 20 Plating layer 30a Magnetic Paste 30 Magnetic layer 40 Conductor Layer 41 Patterned conductor layer

Claims

1. A magnetic paste comprising (A) a magnetic powder and (B) a thermosetting resin, (A) the magnetic powder has an average particle size of 10 μm or less; The moisture content of the magnetic paste is 1000 ppm or less, The magnetic paste may or may not contain an organic solvent; A magnetic paste, the amount of organic solvent contained in the magnetic paste being less than 1.0 mass %.

2. 2. The magnetic paste according to claim 1, wherein the amount of the magnetic powder (A) relative to 100% by volume of the non-volatile components of the magnetic paste is 30% by volume or more.

3. 3. The magnetic paste according to claim 1, wherein the thermosetting resin (B) comprises an epoxy resin (B-1).

4. The magnetic paste according to claim 3, wherein the amount of the epoxy resin (B-1) relative to 100% by mass of the resin component of the magnetic paste is 30% by mass or more.

5. The magnetic paste according to any one of claims 1 to 4, further comprising (C) a hardening accelerator.

6. A magnetic paste described in any one of claims 1 to 5, having a viscosity of 300 Pa·s or less at 25°C.

7. The magnetic paste according to any one of claims 1 to 6, which is for filling through-holes.

8. A hardened product of the magnetic paste according to any one of claims 1 to 7.

9. A circuit board comprising a cured product of the magnetic paste according to any one of claims 1 to 7.

10. A substrate having a through hole formed therein and a magnetic layer filled in the through hole, A circuit board, wherein the magnetic layer comprises a cured product of the magnetic paste according to any one of claims 1 to 7.

11. An inductor component comprising the circuit board according to claim 9 or 10.

12. A step of filling the holes of a substrate having holes formed therein with the magnetic paste according to any one of claims 1 to 7; and hardening the magnetic paste filled in the holes.

13. A method for producing a magnetic paste according to any one of claims 1 to 7, A step of mixing (A) a magnetic powder and (B) a thermosetting resin to obtain a paste-like composition; and drying the paste-like composition in a vacuum at an absolute pressure of 800 Pa or less.

Citation Information

Patent Citations

  • Resin composition, method for producing the resin composition and method for producing coil part

    JP2007002025A

  • Paste composition and magnetic body composition using the same

    JP2009263645A

  • Inductor component, manufacturing method for inductor component, printed wiring board incorporating inductor component

    JP2016197624A

  • Magnetic paste

    WO2020022393A1

  • Magnetic paste

    WO2020105704A1